Meet‐in‐the‐middle attacks on round‐reduced tweakable block cipher Deoxys‐BC. (1st January 2019) - Li, Rongjia; Jin, Chenhui
Abstract : Deoxys‐BC is a tweakable block cipher designed by Jean et al . at ASIACRYPT 2014 within the TWEAKEY framework. Then Deoxys‐BC is used in the CAESAR finalist Deoxys. In this study, the authors consider the security of Deoxys‐BC against meet‐in‐the‐middle attack in the single‐key setting. Using the idea that a chosen tweak difference allows to cancel a difference in the state, they can construct 5‐round meet‐in‐the‐middle distinguisher on Deoxys‐BC‐128‐128 which can be extended to attack on 8‐round Deoxys‐BC‐128‐128. Moreover, they construct 6‐round meet‐in‐the‐middle distinguisher on Deoxys‐BC‐256‐128 which can be extended to attack on 10‐round Deoxys‐BC‐256‐128. As far as the authors know, these are the best attacks against Deoxys‐BC in the single‐key setting.